2020
DOI: 10.21203/rs.3.rs-52300/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral toxicity to high level sodium fluoride causes impairment of autophagy

Abstract: Background: Gingival recession and concomitant alveolar bone resorption are hallmarks of periodontal diseases and excessive fluoride intake has some deleterious effects on teeth, bone and soft tissues. Autophagy is a highly conserved intracellular digestion process that degrades damaged proteins and organelles but the biological roles of autophagy in pathological aspects of oral tissues remain largely unknown. We sought to elucidate the function of autophagy, especially its interplay with apoptosis and oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Exposure of human cementoblast‐like cells (HCEM‐2) to 5 mM sodium fluoride reduced autophagy levels and induced apoptosis, oxidative stress, and inflammation, as evidenced by increased levels of Bax, cleaved caspase‐3, SOD1, and phosphorylated NF‐κB. Thus, exposure to 5 mM sodium fluoride can cause oral toxicity, leading to excessive cellular apoptosis, oxidative stress, and autophagy defects, which exacerbate periodontal tissue damage (Oka et al, 2020).…”
Section: Effect Of Drugs On Periodontal Cell Deathmentioning
confidence: 99%
“…Exposure of human cementoblast‐like cells (HCEM‐2) to 5 mM sodium fluoride reduced autophagy levels and induced apoptosis, oxidative stress, and inflammation, as evidenced by increased levels of Bax, cleaved caspase‐3, SOD1, and phosphorylated NF‐κB. Thus, exposure to 5 mM sodium fluoride can cause oral toxicity, leading to excessive cellular apoptosis, oxidative stress, and autophagy defects, which exacerbate periodontal tissue damage (Oka et al, 2020).…”
Section: Effect Of Drugs On Periodontal Cell Deathmentioning
confidence: 99%
“…One study demonstrated that a high concentration of NaF induces the apoptosis of human cementoblasts through the inhibition of autophagy. Autophagy-related genes ATG5 and Beclin-1 were suppressed, resulting in alveolar bone resorption [101].…”
Section: Fluoride and Periodontal Diseasesmentioning
confidence: 99%